A splice site variant in the SUV39H2 gene in Greyhounds with nasal parakeratosis. (9th February 2018) - Bauer, A.; Nimmo, J.; Newman, R.; Brunner, M.; Welle, M. M.; Jagannathan, V.; Leeb, T.
Summary: Hereditary nasal parakeratosis (HNPK), described in the Labrador Retriever breed, is a monogenic autosomal recessive disorder that causes crusts and fissures on the nasal planum of otherwise healthy dogs. Our group previously showed that this genodermatosis may be caused by a missense variant located in the SUV39H2 gene encoding a histone 3 lysine 9 methyltransferase, a chromatin modifying enzyme with a potential role in keratinocyte differentiation. In the present study, we investigated a litter of Greyhounds in which six out of eight puppies were affected with parakeratotic lesions restricted to the nasal planum. Clinically and histologically, the lesions were comparable to HNPK in Labrador Retrievers. Whole genome sequencing of one affected Greyhound revealed a 4‐bp deletion at the 5′‐end of intron 4 of the SUV39H2 gene that was absent in 188 control dog and three wolf genomes. The variant was predicted to disrupt the 5′‐splice site with subsequent loss of SUV39H2 function. The six affected puppies were homozygous for the variant, whereas the two non‐affected littermates were heterozygous. Genotyping of a larger cohort of Greyhounds revealed that the variant is segregating in the breed and that this breed might benefit from genetic testing to avoid carrier × carrier matings.